GERAKAN FURUDHUL AINIYAH (GEFA) DALAM MEMBENTUK KARAKTER SISWA (Studi Kasus Di Madrasah Aliyah Negeri 10 Jombang): Jurnal Ilmu Pendidikan - Waladah, Ziyanatul; Azah, Nur (Al Tadib : Jurnal Ilmu Pendidikan, 2020)
This article aims to discuss the Furudhul Ainiyah Movement (GEFA) program as a madrasa effort to shape student character. This case studythis research focuses on the application of GEFA in building student character, evaluating the application of GEFA, and supporting and inhibiting factors of GEFA. The results showed that 1) the implementation of the GEFA program was carried out by storing individual students' memorization and practicing worship, 2) evaluation is carried out using a list of assessments according to madrasah standards, and completeness is used as a requirement for students to take semester assessment, 3) Supporting factors are the support for the madrasah organizational structure, facilities and infrastructure, and positive responses from various parties, while inhibiting factors are communication and cooperation with outsiders that are not optimal, the quality of Human Resources (HR) is lacking and professionalism in carrying out their duties, the lack of intrinsic motivation for students to read and memorize Al-Qur'an.